Molecular Characterization of Dengue Virus Serotype 2 Cosmospolitan Genotype From 2015 Dengue Outbreak in Yunnan, China - Jiang, Liming; Ma, Dehong; Ye, Chao; Li, Lihua; Li, Xiaoman; Yang, Jiajia; Zhao, Yujiao; Xi, Juemin; Wang, Xiaodan; Chen, Junying; Pan, Yue; Shan, Xiyun; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
In 2015, a dengue outbreak with 1067 reported cases occurred in Xishuangbanna, a city in China that borders Burma and Laos. To characterize the virus, the complete genome sequence was obtained and phylogenetic, mutation, substitution and recombinant analyses were performed. DENV-NS1 positive serum samples were collected from dengue fever patients, and complete genome sequences were obtained through RT-qPCR from these serum samples. Phylogenetic trees were then constructed by maximum likelihood phylogeny test (MEGA7.0), followed by analysis of nucleotide mutation and amino acid substitution. The recombination events among DENVs were also analyzed by RDP4 package. The diversity analysis of secondary structure for translated viral proteins was also performed. The complete genome sequences of four amplified viruses (YNXJ10, YNXJ12, YNXJ13, and YNXJ16) were 10,742, 10742, 10741 and 10,734 nucleotides in length, and phylogenetic analysis classified the viruses as cosmopolitan genotype of DENV-2. All viruses were close to DENV Singapore 2013 (KX380828.1) and the DENV China 2013 (KF479233.1). In comparison to DENV-2SS (M29095), the total numbers of base substitutions were 712 nt (YNXJ10), 809 nt (YNXJ12), 772 nt (YNXJ13) and 841 nt (YNXJ16), resulting in 109, 171, 130 and 180 amino acid substitutions in translated regions, respectively. In addition, compared with KX380828.1, there were 44, 105, 64 and 116 amino acid substitutions in translated regions, respectively. The highest mutation rate occurred in the prM region, and the lowest mutation rate occurred in the NS4B region. Most of the recombination events occurred in the prM, E and NS2B/3 regions, which corresponded with the mutation frequency of the related portion. Secondary structure prediction within the 3391 amino acids of DENV structural proteins showed there were 7 new possible nucleotide-binding sites and 6 lost sites compared to DENV-2SS. In addition, 41 distinct amino acid changes were found in the helix regions, although the distribution of the exposed and buried regions changed only slightly. Our findings may help to understand the intrinsic geographical relatedness of DENV-2 and contributes to the understanding of viral evolution and its impact on the epidemic potential and pathogenicity of DENV.